CAZyme analysis and functional characterization of a new GH18 chitin hydrolase from Gelidibacter salicanalis PAMC21136 - Lakshan Paudel; Bashu Dev Pardhe; So-Ra Han; Jun Hyuck Lee; Tae-Jin Oh (Carbohydrate Polymer Technologies and Applications)
Gelidibacter salicanalis strains remain poorly understood in terms of their genomic attributes and are rarely reported for the degradation of polysaccharides within the niche. Gelidibacter salicanalis PAMC21136, an Antarctic isolate, was sequenced and functionally annotated. 251 genes were classified into the CAZyme families, which includes the highest number of GH family, highlighting peculiarity towards various macro biopolymers. Further, based on domain architecture and multiple sequence alignment, gene belonging to the family18 glycoside hydrolase was identified as chitinase. The gene encoding chitinase (MBJ7879808.1) was successfully cloned and expressed in Escherichia coli BL21 cells. MBJ7879808.1 demonstrated activity towards colloidal chitin but there was no detectable activity towards microcrystalline crab shell chitin. Enzyme exhibited an exo-pattern of hydrolysis on both colloidal chitin, and shorter chain GlcNAc oligomers namely [(GlcNAc)3, (GlcNAc)4, (GlcNAc)5, and (GlcNAc)6] producing GlcNAc as a single final product. Biochemical characterization revealed an optimum activity at 25 °C and pH 7.0. Mn²⁺ ions significantly enhanced the activity by 1.7-fold. Turnover number (Kcat) was 8.6 min−1 and catalytic efficiency (Kcat/Km) was 2.0ml/mg/min towards the substrate colloidal chitin. These findings expanded the polysaccharide degradation capability of Gelidibacter salicanalis PAMC21136 and highlight the biotechnological potential of the GH18 enzyme towards production of chitooligomers.